Lifelong learning in the global knowledge economy: challenges for developing countries - World Bank (Washington, 2003)
A roadmap for policymakers in developing countries to the key issues and challenges of education in a knowledge economy, this book explores the ways in which lifelong learning systems encourage economic growth. The authors discuss the changing nature of learning and the expanding role of the private sector in education and training worldwide. In a detailed and practical way, they consider the policy and financing options available to governments seeking to meet the lifelong needs of their learners.
Keywords: Economic development